106k views
2 votes
How to solve x2 + 5x - 6 in factoring quadratics

User Luiz Vaz
by
4.6k points

2 Answers

4 votes

Answer:

(x +6) (x-1)

Explanation:

Find the factors of 6 first = 1,6 and 2,3

You must choose the set that when you add them together will make positive 5, but when you multiply them it must make a negative six since the last term is negative

So (x +6 ) (x -1) because if you add 6 + (-1) you get 5

and when you multiply 6 x -1 you get -6

User Howard Hinnant
by
5.1k points
2 votes

Explanation:

here

x² + 5x - 6

= x² + ( 6 - 1 ) x - 6

= x² + 6x - x -6

= x( x + 6 ) - 1 ( x + 6)

= ( x + 6 ) ( x -1 )

User Jsmart
by
4.8k points